DAMPAK PENERAPAN METODE EKSPERIMEN KOLABORASI DENGAN TEAM PRODUCT TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD - Rifayanti, Ria Septiana; Ilhamdi, Moh, Liwa (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2018)
The backgrand of this study is students have low grades because of lack creatifity of the teacher in using method or learning media, so the students find that learning is very boring. The aim of this study is to proof the effect of collaboration Experiment method with Team Product to students score in science at five grade of SDN 3 Sesela in academic year 2018/2019. The kind of this research is Quasi Experiment Desigen. The population of this study is 42 students, the sample of this study is two classes, there are A five grade consist of 21 students and B five grade with 21 studenst. The technique of collecting data in this study is using test and documentation. The posttest data is using t-test in polled varians and N-gain test to knowing the difference two groups significantly. Based on analysis statistic the result of tcount is 2,699 > ttable 2,021 (assigenment of two groups) to significance level 5% which is mean that there is differences between students score in experiment class and control and control class in science at five grade of SDN 3 Sesela in academic year 2018/2019. The difference is 8,45 (71,02-62,57). The increasing of science score at 5 grades of SDN 3 Sesela academic year 2018/2019 is knowing mean <g> experiment class 0,451 medium level. Which is higher then control class is 0,206 low level. The conclusing is there is effect of implementation collaboration experiment method with team product to students score at 5 grade of SDN 2 Sesela academic year 2018/2019.